1999
DOI: 10.1002/(sici)1099-0690(199901)1999:1<167::aid-ejoc167>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Some Reactions of the Tricarbonylchromium Complexes of 1,3-Indandione and Ninhydrin

Abstract: The syntheses and characterization of the tricarbonylchromium complexes of 1,3‐indandione and ninhydrin are described. As the direct complexation proved unsuccessful, the acetal route was tried. Although some complexes were obtained, complex deacetalization did not work in the case of ninhydrin. Finally, the oxidation of tricarbonyl(η6‐1,3‐indandione)chromium(0) with dimethyldioxirane gave the ninhydrin complex in 75% yield in equilibrium with the indantrione complex. The latter reacts in hetero Diels‐Alder re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…5.47 (2d, 3 J ϭ 6.7, 3 J ϭ 5.8 Hz, 2 H, 4-H, 6-H), 6.18 (dd, 3 J ϭ 6.3, 3 J ϭ 6.4 Hz, 1 H, 5-H) ppm. 13 Treatment of rac-3 with 1-Lithio-1-methoxyallene: GP I. Butyllithium in hexane (1.6 , 2.5 mL, 3.9 mmol) was added at Ϫ78°C to 1-methoxyallene (281 mg, 4.0 mmol) in diethyl ether (15 mL) and warmed to Ϫ30°C over 45 min. [39,40] Treatment of rac-3 with 1-Lithiocyclopentene: GP I.…”
Section: General Procedures For the Dianionic Oxy-cope Rearrangement Imentioning
confidence: 99%
See 1 more Smart Citation
“…5.47 (2d, 3 J ϭ 6.7, 3 J ϭ 5.8 Hz, 2 H, 4-H, 6-H), 6.18 (dd, 3 J ϭ 6.3, 3 J ϭ 6.4 Hz, 1 H, 5-H) ppm. 13 Treatment of rac-3 with 1-Lithio-1-methoxyallene: GP I. Butyllithium in hexane (1.6 , 2.5 mL, 3.9 mmol) was added at Ϫ78°C to 1-methoxyallene (281 mg, 4.0 mmol) in diethyl ether (15 mL) and warmed to Ϫ30°C over 45 min. [39,40] Treatment of rac-3 with 1-Lithiocyclopentene: GP I.…”
Section: General Procedures For the Dianionic Oxy-cope Rearrangement Imentioning
confidence: 99%
“…We have for some time been interested in complexes with anellated cyclobutane rings, and have found the complexes of benzocyclobutenone and benzocyclobutenedione to be key compounds in our investigations. [2,13] Nucleophilic additions at the oxo groups of these complexes were the basis of highly selective, aniondriven reactions such as the distal ring-opening to orthoquinodimethane intermediates, followed by cycloaddition, [14Ϫ18] an anionic ring-expansion to indanone systems upon acyl anion addition, [19] anionic 1-vinylcyclobutenolϪcyclohexadienol rearrangement, [19] and [ ated only one of two expected reaction products was obtained. As an explanation of this remarkable selectivity we considered a chelation effect of the intermediate bis(enolate) involving the 3-methoxy substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 2 under equally mild reaction conditions undergoes alkenyllithium diaddition reactions followed by dianionic oxy-Cope rearrangements [23][24][25][26]. Complexes 3 and 4 of 1,2-indandione and 1,3-indandione also undergo nucleophilic attack from the face opposite to the tricarbonylchromium group [27,28]. In contrast to 2 and in contrast to uncoordinated 1,2-indandione the 1,2-indandione complex 3 so far did not undergo a dianionic oxy-Cope rearrangement, presumably because of the facile enolate formation [27].…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to 2 and in contrast to uncoordinated 1,2-indandione the 1,2-indandione complex 3 so far did not undergo a dianionic oxy-Cope rearrangement, presumably because of the facile enolate formation [27]. Indantrione complex 5 undergoes hetero Diels-Alder cycloaddition at the central carbonyl group with attack of the diene from the face opposite to the tricarbonylchromium group [28]. In order to avoid the enolate formation, we became interested in the synthesis of non-enolizable analogues of 3, which might serve as substrates in these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations by Butenschon and co-workers showed that ninhydrin is interchangeably converted to either ketal intermediates 288 or 287, of which both are leading to 1,2,3-tris(ethylenedioxy)indane 289, the route via 287 giving higher yield (Scheme 92). 334 In a related study, they found that the photolytic decarbonylation of 288 occurs smoothly during irradiation to give 290. Harrison et al found that a mixture of thiophene in aqueous sulfuric acid (75% v/v) and ninhydrin produces low yields of three products (304, 306 and 307): firstly, the typical reaction of a ketone with thiophene produces the dithienyldiketone 304 (minor observed product, 0.8%), which experiences acid-induced rearrangement to the diastereomeric diol intermediate 305.…”
mentioning
confidence: 99%